Comparison of anthropometric and functional characteristics of elite male Iranian fencers in three weapons - Abdollah, S.; Khosrow, E.; Sajad, A. (International Journal of Applied Sports Sciences, 2014)
Purpose: Recognizing the characteristics of elite athletes has a valuable significance in any sport for two reasons: 1) It leads to a high-level performance; and 2) this recognition helps us to determine the weaknesses and strengths of athletes. The present study was designed to compare the anthropometric characteristics, aerobic and anaerobic capacities of elite male Iranian fencers in three different categories (epee, foil and sabre). Mater ials and methods: For this purpose, 24 fencers of Iran national senior fencing team were chosen and their anthropometric characteristics, somatotype, grip power, aerobic and anaerobic capacity of leg and hand, were measured. Results: Statistical analyses of data showed significant differences (p.0.05) between lean body mass, weight and efficient hand length (EHL) of sabre and foil fencers. In addition, significant differences (p. 0.05) were found between EHL and the difference between the length of two opened arms and height of epee and foil fencers. The amount of these variables were higher in epee than foil fencers. Aerobic capacities of epee and foil fencers were higher than sabre ones (p.0.05). The dominant somatotype for three categories was endomorphic mesomorph. Conclusion: Based on the physiological and some anthropometric differences among the three fencing categories found in the present study, it could be concluded that the training programs and athlete selection criteria should be different among the fencing categories.